Real-time visual servo control of a robot using uncalibrated cameras - Jiao, Cai Xiao (2008)
With rapid development of computer technology and the industrial call for intelligent robots to play an increasing role than ever, visual servo control of the robot has become an active area of research. In this thesis, we outline the state of the art in this growing research field. To test the feasibility of thee proposed techniques, both simulation and real experiments are conducted accordingly under the environment of MATLAB and the Microsoft VC++ integrated development environment. The results show the possibility of applying the proposed methods in the real-world application. The proposed techniques absolutely do not require any model or calibration because there is no requirement to reconstruct three-dimensional information. The cameras can be shifted even during tracking.